2022
DOI: 10.1021/acsbiomaterials.1c01290
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Assessment Reveals a Higher Force per Contact Area on Fibrous Structures Compared to Flat Substrates

Abstract: The distribution and density of ligands have a determinant role in cell adhesion on planar substrates. At the same time, planar surfaces are nonphysiological for most cells, and cell behavior on planar and topographical surfaces is significantly different, with fibrous structures being the most natural environment for cells. Despite phenomenological examinations, the role of adhesion ligand density in the fibrous scaffold for cell adhesion strength has so far not been assessed. Here, we established a method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…In this study, the cell adhesion process for PβAE1.5 and its copolymer films show active adhesion between the cells and the surface of the films. This can be due to the suitable hydrophilicity, the surface charge and chemical structure of PBAE1.5 to interact with fibroblast cells [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the cell adhesion process for PβAE1.5 and its copolymer films show active adhesion between the cells and the surface of the films. This can be due to the suitable hydrophilicity, the surface charge and chemical structure of PBAE1.5 to interact with fibroblast cells [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have identified that the distinctive morphology of polymer scaffolds, including anisotropic structures, can induce a contact-induced effect, leading to cell alignment and migration along the direction of the pores. [88][89][90][91][92] Numerous human tissues, such as muscles, [93] blood vessels, [88] skin, [94] and nerves, [95] exhibit directional cell arrangements. Therefore, scaffolds with oriented pore structures possess greater potential for guiding and promoting cell growth, supporting cell alignment, and facilitating proliferation compared to scaffolds with random pore structures.…”
Section: Oriented Porous Polymer Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…15 This technique proved to be very versatile and allowed for reversibly formed colloidal probes [16][17][18] and the aspiration of sessile cells on a substrate, which allows for quantitative characterization of their detachment forces. [19][20][21][22][23] For biological applications, fluidic force microscopy is not limited to the determination of adhesion forces of cells on various substrates. Currently, intracellular injection or sampling of organelles under precise force control are actively pursued by this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The development of fluidic force microscopy originated less than 15 years ago 15 . This technique proved to be very versatile and allowed for reversibly formed colloidal probes 16–18 and the aspiration of sessile cells on a substrate, which allows for quantitative characterization of their detachment forces 19–23 . For biological applications, fluidic force microscopy is not limited to the determination of adhesion forces of cells on various substrates.…”
Section: Introductionmentioning
confidence: 99%